Multa qualificada e o crime de sonegação fiscal: uma investigação sobre a pluralidade de respostas sancionatórias e o espectro de proteção do princípio do ne bis in idem - Pereira, Patrícia Gondim Moreira (2019)
The main purpose of the proposed investigation is to investigate whether the cumulation of punitive tax sanctions arising from the practice of the same fact would be compatible with the rational principle of ne bis in idem, in its material or subtantial aspects, the so-called ne bis in idem puniri. The common grounds between the tax criminal offense and the criminal tax infraction, some of its common guiding principles and the historical tril of the ne bis in idem, are analyzed, as well as their basis, meaning and criteria of applicability. There are also solutions for situations of overlap between the state control spheres with punitive exacerbation by the application of more than one saction with similar ends. And, at the end, the research suggests contributions to the (re)construction of the ne bis in idem principle in the Brazilian punitive system, specifically regarding tax law